High levels of pathological jaundice in the first 24 hours and neonatal hyperbilirubinaemia in an epidemiological cohort study on the Thailand-Myanmar border. - Laurence Thielemans (Public Library of Science (PLoS), 2021)
Population risks for neonatal hyperbilirubinaemia (NH) vary. Knowledge of local risks permits interventions that may reduce the proportion becoming severe. Between January 2015 and May 2016, in a resource-limited setting on the Thailand-Myanmar border, neonates from 28 weeks' gestation were enrolled into a prospective birth cohort. Each neonate had total serum bilirubin measurements: scheduled (24, 48, 72 and 144 hours of life) and clinically indicated; and weekly follow up until 1 month of age. Risk factors for developing NH were evaluated using Cox proportional hazard mixed model. Of 1710 neonates, 22% (376) developed NH (83% preterm, 19% term). All neonates born <35 weeks, four in five born 35-37 weeks, and three in twenty born ≥38 weeks had NH, giving an overall incidence of 249 per 1000 livebirths [95%CI 225, 403]. Mortality from acute bilirubin encephalopathy was 10% (2/20) amongst the 5.3% (20/376) who reached the severe NH threshold. One-quarter (26.3%) of NH occurred within 24 hours. NH onset varied with gestational age: at a median [IQR] 24 hours [24, 30] for neonates born 37 weeks or prematurely vs 59 hours [48, 84] for neonates born ≥38 weeks. Risk factors for NH in the first week of life independent of gestational age were: neonatal G6PD deficiency, birth bruising, Sgaw Karen ethnicity, primigravidae, pre-eclampsia, and prolonged rupture of membranes. The genetic impact of G6PD deficiency on NH was partially interpreted by using the florescent spot test and further genotyping work is in progress. The risk of NH in Sgaw Karen refugees may be overlooked internationally as they are most likely regarded as Burmese in countries of resettlement. Given high levels of pathological jaundice in the first 24 hours and overall high NH burden, guidelines changes were implemented including preventive PT for all neonates <35 weeks and for those 35-37 weeks with risk factors.